Assessment of depression and anxiety in Tunisian patients with chronic diseases: impact on quality of life and medication adherence - Farah, Cherif; Rim, Masmoudi; Chourouk, Frikha; Mariam, Abdelkefi; Fatma, Guermazi; Meziou, Emna; Ines, Feki; Jawaher, Masmoudi (Frontiers in Psychiatry, 2025)
IntroductionChronic illness affects patients’ quality of life and often leads to underdiagnosed psychological issues, which can impact treatment adherence. This study aimed to assess quality of life in Tunisian patients with chronic diseases, screen for anxiety and depression, and evaluate their effect on medication adherence.MethodsWe conducted a cross-sectional study including 170 patients consulting at the National Social Security Fund for chronic conditions, from September to November 2022. Quality of life was assessed using the Short Form 12 Health Survey, anxiety and depression using the Hospital Anxiety and Depression scale, and treatment adherence using the Morisky, Green, and Levine scale.ResultsAmong the 170 patients included in this study, 116 were women (68.2%), with a female-to-male ratio of 2.14. The mean age was 60 years and 5 months ± 9.85 years. The most common conditions were cardiovascular (71.7%), endocrine (64.7%), and pulmonary diseases (40.5%). The prevalences of depression and anxiety were 51.8% and 47%, respectively. Quality of life was impaired, with mean physical and mental scores of 35.05 ± 9.69 and 44.32 ± 11.13, respectively. Anxiety was more prevalent among women (p<0.001) and individuals under 60 years of age (p=0.009). Depression and anxiety were negatively correlated with quality of life. Depressive symptoms were associated with lower levels of treatment adherence (p=0.049).ConclusionAnxiety and depression were frequent among patients with chronic diseases and were associated with poorer quality of life and lower treatment adherence. These findings underscore the burden of psychological distress in this population and highlight its detrimental effects on both well-being and disease management.